2015
DOI: 10.1038/srep18204
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of Perilla frutescens in activated human neutrophils through two independent pathways: Src family kinases and Calcium

Abstract: The leaves of Perilla frutescens (L.) Britt. have been traditionally used as an herbal medicine in East Asian countries to treat a variety diseases. In this present study, we investigated the inhibitory effects of P. frutescens extract (PFE) on N-formyl-Met-Leu-Phe (fMLF)-stimulated human neutrophils and the underlying mechanisms. PFE (1, 3, and 10 μg/ml) inhibited superoxide anion production, elastase release, reactive oxygen species formation, CD11b expression, and cell migration in fMLF-activated human neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 51 publications
0
32
0
Order By: Relevance
“…The increase in intracellular calcium plays an important role in several functions in a variety of cell types, including neutrophils, for example, activating calcium‐dependent events, such as PKC activation . Our study demonstrated that EPI and EPIIS reduced the prolonged increase in calcium mobilization into the cytosolic compartment after activation of neutrophils with fMLP.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The increase in intracellular calcium plays an important role in several functions in a variety of cell types, including neutrophils, for example, activating calcium‐dependent events, such as PKC activation . Our study demonstrated that EPI and EPIIS reduced the prolonged increase in calcium mobilization into the cytosolic compartment after activation of neutrophils with fMLP.…”
Section: Discussionmentioning
confidence: 52%
“…The modulation of this system could attenuate the inflammatory reactions because of HOCl, the most powerful oxidant produced by human neutrophils, with the potential to cause considerable tissue damage in many inflammatory diseases. [29] The increase in intracellular calcium plays an important role in several functions in a variety of cell types, including neutrophils, [30] for example, activating calcium-dependent events, such as PKC activation. [3] Our study demonstrated that EPI and EPIIS reduced the prolonged increase in calcium mobilization into the cytosolic compartment after activation of neutrophils with fMLP.…”
Section: Discussionmentioning
confidence: 99%
“…Upon activation, neutrophils release antimicrobial proteins in a process referred to as degranulation. Elastase release was measured spectrophotometrically using a synthetic elastase substrate, methoxysuccinyl-Ala-Ala-Pro-Val-p-nitroanilide 19,20. Human neutrophils suspensions (6×10 5 cells/mL) were preincubated in HBSS containing CaCl 2 (1 mM) and elastase substrate (0.1 mM) at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Perilla frutescens (PF) is a common herb which has been widely used as traditional Chinese food and medicine . It has been reported that P. frutescens has good pharmacological activities such as allergy relief, anti‐inflammatory, anti‐oxidation and asthma therapy . The main effective components from different parts of PF mainly contained phenolic compounds, flavonoids and triterpenes .…”
Section: Introductionmentioning
confidence: 99%